Uses of Microalgae in Aquaculture - A. Muller-Feuga; R. Robert; C. Cahu; J. Robin; P. Divanach (Blackwell Publishing, 2025)
The culture of microalgae is of fundamental importance to commercial hatcheries rearing marine molluscs, since they are currently the only suitable food source. Molluscs, unlike fish and crustaceans, are fed microalgae directly. Consequently, mollusc development is closely related to the quantity and quality of phytoplankton produced. Microalgal cultures are necessary because the concentration of natural phytoplankton in the seawater used in the hatchery is generally insufficient for optimum growth of the high densities of larvae and juveniles reared. Moreover, to avoid bacterial diseases, the seawater used for rearing is purified, usually by fine filtration (0.2–1.0 m) and/or ultraviolet (UV) treatment (Robert & Gérard 1999). This eliminates almost all of the natural phytoplankton, which must then be replaced by dense artificial cultures.